2022
DOI: 10.1016/j.japh.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID-19 outbreak in community pharmacists: A longitudinal study

Abstract: Background COVID-19 has negatively impacted the mental health of frontline health care workers, including pharmacists. Objective(s) The aim of this longitudinal study was to assess the psychological impact of the COVID-19 outbreak in French owner community pharmacists. Methods We carried out a postal-based survey to assess the psychological difficulties of the COVID-19 outbreak in French owner community pharmacists based on three psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In particular, there was a significant decrease in anxiety levels at the end of the first wave, which is consistent with the results of some studies conducted worldwide (34)(35)(36). According to the literature (32,34), such a decrease may be attributed to greater control over the pandemic, more knowledge and resources for treating patients, greater familiarity with the new working routine, and decreased stigma associated with healthcare workers.…”
Section: Discussionsupporting
confidence: 87%
“…In particular, there was a significant decrease in anxiety levels at the end of the first wave, which is consistent with the results of some studies conducted worldwide (34)(35)(36). According to the literature (32,34), such a decrease may be attributed to greater control over the pandemic, more knowledge and resources for treating patients, greater familiarity with the new working routine, and decreased stigma associated with healthcare workers.…”
Section: Discussionsupporting
confidence: 87%
“…Nearly two thirds ( n = 164, 63.1%) of respondents reported that COVID-19 was having an impact on them personally. There was stronger agreement reported from female members of the workforce ( n = 119 66.9%), and this could be due to “traditional” caregiving roles for younger families, which creates dual role pressure; studies also noted this factor on the effect of the pandemic on female members of the workforce [ 14 , 15 , 16 ]. Areas where there were greater impacts focused around pharmacist wellbeing and the use or availability of Personal Protective Equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacist workforce are predominantly women, who have also reported increased stress, particularly regarding childcare arrangements, which has often meant balancing family responsibilities in addition to greater work responsibilities [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among their medical staff, 36% had insomnia symptoms [40]. Lange's initial findings regarding the impact of the COVID-19 epidemic on mental health also indicated significant psychological disorders among healthcare professionals [27], including post-traumatic stress disorder in 23.1% of them during lockdown, then 16.4% two years later [26]. In the French study by Ghesquiere, 17.9% (n = 37) of the population used anxiolytics.…”
Section: The Mental Health Of Pharmacists Needs Concernmentioning
confidence: 99%
“…In addition, several individual antecedents were identified. In France, there are only two publications by Lange on the mental health of dispensing pharmacists in 2020 and 2022 in the same cohort [26,27]. Both studies used the perceived stress scale (PSS), the impact of event scale-revised (IES-R), and the Maslach burnout inventory (MBI).…”
Section: Introductionmentioning
confidence: 99%